A feminist reading of Shakespearean tragedies: frailty, thy name is woman - M. Ayub Jajja (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Literary texts are loaded with ideologies, sometimes overtly and sometimes covertly. Shakespeare's plays, both tragedies and comedies are perfect specimens of art and literature. Theories and principles of pure art and form can be deduced from them. On the surface, they seem to be structured by issues like love, jealousy, hatred, wars, intrigues, human failures and failings. But deep down these texts are the carriers of ideologies. They, at one level, project the binary opposition between male and female, in which male pair is privileged. Shakespeare's plays are not lacking in women with positive human qualities, and some of them are presented with qualities and attributes at par with men, but on the whole these texts disseminate and project the historical and conventional perception of woman, as lesser and negative stereotype, and portray them from the patriarchal perspective. The present study intended to investigate the portrayal of women in Shakespeare's major tragedies. The study is based upon the exhaustive analysis of the major tragedies of Shakespeare (Hamlet, Macbeth, King Lear, Antony and Cleopatra and Romeo and Juliet) in the light of deconstructive Feminism. The main hypothesis of the study is that women in Shakespearean tragedies are portrayed and presented as lesser and negative stereotypes and these texts have reinforced and strengthened the patriarchy and patriarchal values.
Keywords: 330; patriarchy; boggler; morsel; dish; frailty; headstrong; sovereign; emperor; god